What Works for Working Women? : Understanding Female Labor Force Participation in Urban Bangladesh - Kotikula, Aphichoke; Hill, Ruth; Raza, Wameq Azfar (World Bank, Dhaka, 2019)
This paper explores the factors that constrain women in slums and low-income neighborhoods in Dhaka from engaging in the labor market and supplying their labor to wage earning or self-employment. It uses unique individual-level data on labor market participation, time-use, norms, and skills, both cognitive and noncognitive. The data reconfirms well-known patterns associated with FLFP: that is, it is higher in low-income neighborhoods and among women with little education, and younger unmarried women. The paper also highlights the correlation between soft skills and type of work. The paper also quantifies the important correlation between the need for childcare, as well as safety in public spaces and in the workplace.